Identifying chemical carcinogens and assessing potential risk in short-term bioassays using transgenic mouse models. - Tennant, R W (1995)
Cancer is a worldwide public health concern. Identifying carcinogens and limiting their exposure is one approach to the problem of reducing risk. Currently, epidemiology and rodent bioassays are the means by which putative human carcinogens are identified. Both methods have intrinsic limitations: they are slow and expensive processes with many uncertainties. The development of methods to modify specific genes in the mammalian genome has provided promising new tools for identifying carcinogens and characterizing risk. Transgenic mice may provide advantages in shortening the time required for bioassays and improving the accuracy of carcinogen identification; transgenic mice might now be included in the testing armamentarium without abandoning the two-year bioassay, the current standard. We show that mutagenic carcinogens can be identified with increased sensitivity and specificity using hemizygous p53 mice in which one allele of the p53 gene has been inactivated. Furthermore, the TG.AC transgenic model, carrying a v-Ha-ras construct, has developed papillomas and malignant tumors in response to a number of mutagenic and nonmutagenic carcinogens and tumor promoters, but not to noncarcinogens. We present a decision-tree approach that permits, at modest extra cost, the testing of more chemicals with improved ability to extrapolate from rodents to humans.